Evaluation of Iodine Transmutation Rate in the High Flux Reactor BR-2 - L. Omeir; N. Amrani; A. Boucenna (Algerian Journal of Research and Technology (AJRT), 2021)
In this study, we evaluate the transmutation rate of the long-lived fission product Iodine to the stable Xenon under irradiation in the high flux reactor BR2. The Iodine transmutation rate and the evolution of Xenon mass under irradiation were numerically simulated using ChainSolver 2.34 code.